PELATIHAN PEMBUATAN TOTEBAG DENGAN MENGGUNAKAN TEKNIK ECOPRINT DI DESA KARANGPATRI - Anisah, Nur; Khatimah, Husnul; Supratno, Setyo (An-Nizam, 2023)
Karangpatri village is one of the villages in pebayuran district, Bekasi Regency. Therefore, in this community service activity the author carried out a training program for making totebags using the ecoprint technique as community empowerment with the hope that this activity could become a goal of increasing insight, skills and an economic business opportunity for women in karangpatri village by utilizing natural materials around us, such as leaves, flowers, stems, or other parts that have color pig ments and using certain fabric media. The KKN program carried out by this author aims to develop innovation in making totebags using the Ecoprint technique in karangpatri village socialization and training activities for making totebags were carried out Through community service activities or KKN (Real Work Lecture) activities, this time we invite PKK mothers in karangpatri village to take part in socialization and also take part in making Totebags with this activity of making Totebags using the Ecoprint Technique which is simple and easy, it is hoped that it can make the village community become more interested in making Totebags using the Ecoprint Technique.